Soil management on the table - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Conservation agriculture, based on sustainable soil management techniques, is the subject of the first world congress in French, English and Spanish on this topic, to be held from 1-5 October 2001 in Madrid, Spain. The meeting is being...